Are some health benefits of palmitoleic acid supplementation due to its effects on 5′ adenosine monophosphate‐activated protein kinase (AMPK)?. Issue 12 (December 2015) - Morse, Nancy
Abstract : In preclinical and human epidemiological and intervention trials, palmitoleic acid (POA) has shown anti‐inflammatory and lipid lowering effects linked to prevention of metabolic syndrome including cardiovascular disease and insulin resistance associated with diabetes and obesity. Similar benefits have been reported following AMPK activation suggesting a convergent mode of action. A comparison of POA supplementation metabolic effects and AMPK activation impact reveals a multitude of similarities. This observation suggests that POA could be exerting at least some of its beneficial effects through AMPK activation. Preclinical studies have reported increased cellular AMPK transcription and activated AMPK levels and activity following POA treatment. A plausible explanation of how POA may activate AMPK has been reported. Further research will establish the role of POA in AMPK activation and its effects on specific biochemical activities, overall metabolism and health.